(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Formulaic language expressions (FLEs) play a significant role in communication, combining predictability and fluency in both spoken and written forms. This article explores the linguistic features of FLEs, examining their structures, functions, and the cognitive mechanisms behind their use. Through a review of relevant literature, qualitative analysis, and observational data, the study aims to illuminate how FLEs contribute to natural language processing and communication efficiency. By highlighting their characteristics and examining case studies, the paper offers insights into the importance of FLEs in both everyday and specialized language use.